Psychological Characteristics of Children’s Motivation for Participating in Artistic Gymnastics - Ольга Б. Крушельницкая; Вероника Э. Терентьева (Rossijskij psihologičeskij žurnal., 2020)
Introduction. Sport motivation is generally considered in educational research, while its psychological foundations remain understudied. This study examines the impact of children’s sociometric status, anxiety level, and family background, including parental attitudes, on their motivation for participating in artistic gymnastics. Methods. The study sample comprised 95 preschool-aged and early school-aged children participating in artistic gymnastics for more than a year. In order to identify the psychological and socio-psychological characteristics of children’s motivation, the following measurement tools were used in this study: (a) the Parental Attitudes Questionnaire (A. Ya. Varga, V. V. Stolin), (b) the Choose the Right Face test for the assessment of anxiety (R. Tamml, M. Dorky, V. Amen), (c) the Children’s Manifest Anxiety Scale, CMAS (modified by A. M. Prikhozhan), (d) the measure for assessing the level of students’ sport motivation by N. G. Luskanova (modified by O. N. Stepanova & A. N. Volkova), (e) sociometry, and (f) statistical data processing. Results. The findings indicated that there are significant differences in characteristics of children with different levels of motivation. Depending on the parenting style, children with a high level of sport motivation had average or high levels of anxiety and high or low sociometric status in their training groups. Parental attitudes towards these children are characterized by a high level of acceptance and cooperation, which manifest itself in a positive attention to their interests, respect, and encouragement of independence and initiative. Discussion. The results of this study contribute to our understanding of psychological conditions for optimizing children’s sport motivation, open up opportunities for further research on the socio-psychological factors for children’s sports motivation, and may be readily used in training programs to improve the psychological competence of sports coaches.